FORMATION OF COGNITIVE AND INTELLECTUAL COMPETENCE OF VOLUNTEERS - Fedorov, M. (SWorld-Ger Conference proceedings, 2024)
The article clarifies the essence of the concept of cognitive-intellectual competence as an important factor in the successful work of a volunteer. The structural components of the volunteer’s competence have been determined. The main qualities of a volun